Closing the feedback loop : can technology bridge the accountability gap? - Gigler, Björn-Sören; Bailur, Savita (Directions in development (Washington, D.C.). Public sector governance., 2014)
This book is a collection of articles, written by both academics and practitioners as an evidence base for citizen engagement through information and communication technologies (ICTs). In it, the authors ask: how do ICTs empower through participation, transparency and accountability? Specifically, the authors examine two principal questions: Are technologies an accelerator to closing the ""accountability gap""--The space between the supply (governments, service providers) and demand (citizens, communities, civil society organizations or CSOs) that requires bridging for open and collaborative